KEWIRAUSAHAAN PENUNJANG EKONOMI KREATIF DI MASA PANDEMI - Yopy Ratna Dewanti; Eko Hadi Prayitno; Dingot Hamonangan Sitanggang; Arifin Setiabudi; Damdam Damiyana (JURNAL ABDIMAS PLJ, 2021)
The function and purpose of national education is to develop and shape the character and civilization of a dignified nation in the context of the intellectual life of the nation, aiming to develop the potential of students to become human beings who are devoted to both parents and useful for the homeland and religion. In order to be more deeply embedded in students' souls, the process of implementing character education, entrepreneurship education, and creative economy needs to be carried out through good planning and an effective learning approach and carried out jointly by all school members, through integration in subjects, local content and activities. -activities in self-development (Depdiknas, 2006). Entrepreneurship education aims to develop an entrepreneurial spirit, informing that the traits developed are responsible (94%) and risk-taking (97%). As well as creativity and innovation (99%).Keywords: entrepreneurship education, creative economy, economic subjects